Relevansi Legalitas Akad Syariah dalam Mewujudkan Kepastian Hukum dan Keadilan Ekonomi Islam - Bagus Setya Puji Saputra; Muhammad Habib Nasrullah; Nur Aziz Muslim; Muhammad Haris Abdul Hakim (Indo Publishing, 2025)
This study aims to examine the legality of contracts (akad) in sharia agreements using a normative-juridical approach and a conceptual review based on Islamic legal principles. The main focus lies on the position of akad as an essential element in establishing legal relationships between parties in sharia-based transactions. The analysis highlights the requirements for a valid akad, including its essential elements such as offer and acceptance (ijab qabul), legal subjects (contracting parties), contract objects, and compliance with sharia principles. The findings indicate that the validity of a contract in Islamic law is not solely based on mutual agreement but must also conform to values of justice, public interest (maslahah), and the prohibition of invalid elements such as gharar (uncertainty), maysir (gambling), and riba (usury). These results affirm that in Islamic economic practices, fulfilling the legal aspects of akad is fundamental to ensuring legal certainty and protecting the parties involved. The study recommends strengthening regulatory frameworks and fatwas that support contract practices aligned with maqashid shariah to enhance legal integrity within the sharia financial system.